2012
DOI: 10.1016/j.ejca.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of TP53 are associated with a poor outcome for patients with hepatocellular carcinoma: Evidence from a systematic review and meta-analysis

Abstract: Background The prognostic significance of p53 aberration in hepatocellular carcinoma (HCC) remains inconclusive. This review aimed to provide comprehensive evidence on the association of p53 alterations with recurrence-free survival (RFS) and overall survival (OS) in HCC patients. Methods Systematic literature searches were conducted until July 2010. Meta-analysis was performed to estimate prognostic effects of p53 alterations on patient outcomes in HCC. Sensitivity and subgroup analyses were also conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 50 publications
13
89
0
Order By: Relevance
“…Many studies have proven that p53 is frequently mutated in human hepatocellular carcinoma (HCC), and the mutations in p53 gene were correlated to tumor stage [10,11]. Systematic review and meta-analysis demonstrated that HCC patients with p53 mutation have a shorter recurrence-free survival and overall survival than patients with wild-type p53 or low/ undetectable p53 expression [12]. All these revealed that p53 mutation played a pivotal role in the pathogenesis of HCC.…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have proven that p53 is frequently mutated in human hepatocellular carcinoma (HCC), and the mutations in p53 gene were correlated to tumor stage [10,11]. Systematic review and meta-analysis demonstrated that HCC patients with p53 mutation have a shorter recurrence-free survival and overall survival than patients with wild-type p53 or low/ undetectable p53 expression [12]. All these revealed that p53 mutation played a pivotal role in the pathogenesis of HCC.…”
Section: Introductionmentioning
confidence: 98%
“…Mutant forms of p53 have a prolonged halflife, which favors intranuclear accumulation, becoming detectable immunohistochemically (Zhou et al, 2006). In several studies, the overexpression of p53 in the serum or liver tissues of HCC patients was associated with a poorer prognosis, a shorter survival time and tumor recurrence (Caruso et al, 1999;Hsia et al, 2000;Qin et al, 2001;Liu et al, 2012). In our research, overexpression of p53 was found in 44% of HCCs.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, Gatchel et al [23] found that insulin-like growth factor (IGF) pathway was involved in SCA7 disease. There have been many studies that reported that both TP53 and IGF play a critical role in the occurrence and prognosis of HCC [24][25][26][27][28]. Recent studies demonstrated that ATXN7 was associated with breast cancer susceptibility and prognosis of RCC [15,16].…”
Section: Discussionmentioning
confidence: 99%